Literasi Pengaruh Digital Lingkungan Kerja Dan Budaya Organisasi Terhadap Produktivitas Kerja Karyawan Melalui Kepuasan Kerja : Studi Pada Karyawan PT.EUDE Indonesia - Bambang Wahyudiyono; Yuli Budiati; Djoko Santoso (Jurnal Bingkai Ekonomi (JBE), 2024)
This type of research is explanatory research. The population of this study were employees of the production department of PT. EUDE Indonesia, Semarang. The sample taken was 80 employees. The sampling technique used was a simple random sample. The data collection method used was a questionnaire. The analysis technique used is PLS (Partial Least Square). Research results show that:The work environment has a positive and significant effect on job satisfaction, Organizational culture has a positive and significant effect on job satisfaction,Job satisfaction has a positive and significant effect on work productivity,The work environment has a positive and significant effect on work productivity,Organizational culture has a positive and significant effect on work productivity.The work environment has a positive and significant effect on employee work productivity with job satisfaction as a mediating variable,Organizational culture has a positive and significant effect on employee work productivity with job satisfaction as a mediating variable.